English Proficiency Aspirations among Nepalese EFL Students - Tiwari, Hari Prasad (Fakultas Sastra - Universitas Muslim Indonesia, 2023)
English is regarded as a key to different opportunities and a language of high status in Nepal. Whether by desire or compulsion, English fascination of a large number of students in Nepal is increasing. This study investigated the factors that motivated Nepalese learners of English as a Foreign Language (EFL) to attain a higher level of English proficiency. The participants consisted of 24 master’s level EFL students from four constituent campuses of Tribhuvan University. The researcher used purposive sampling to select the participants. The study employed interview as data collection technique. The data was analyzed using thematic approach of qualitative data analysis. The study revealed that Nepalese EFL students aspired to achieve English proficiency for five reasons, such as to meet their educational expectations access, to pursue better career opportunities and global competitiveness, to improve their economic and social status and to access technology and innovation. The study contributes to the understanding of the evolving dynamics of language proficiency in a globalized world, urging educators and policymakers to consider the diverse factors that influence language acquisition for a holistic approach to language education.